If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(x + -7) + 3 = 2(x + 9) Reorder the terms: -1(-7 + x) + 3 = 2(x + 9) (-7 * -1 + x * -1) + 3 = 2(x + 9) (7 + -1x) + 3 = 2(x + 9) Reorder the terms: 7 + 3 + -1x = 2(x + 9) Combine like terms: 7 + 3 = 10 10 + -1x = 2(x + 9) Reorder the terms: 10 + -1x = 2(9 + x) 10 + -1x = (9 * 2 + x * 2) 10 + -1x = (18 + 2x) Solving 10 + -1x = 18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 10 + -1x + -2x = 18 + 2x + -2x Combine like terms: -1x + -2x = -3x 10 + -3x = 18 + 2x + -2x Combine like terms: 2x + -2x = 0 10 + -3x = 18 + 0 10 + -3x = 18 Add '-10' to each side of the equation. 10 + -10 + -3x = 18 + -10 Combine like terms: 10 + -10 = 0 0 + -3x = 18 + -10 -3x = 18 + -10 Combine like terms: 18 + -10 = 8 -3x = 8 Divide each side by '-3'. x = -2.666666667 Simplifying x = -2.666666667
| 0.5n+2=4 | | 9y-137=-y-7 | | x-1/x-24/5=0 | | X=3-.5 | | 2x^3+x=3 | | 56-16x=-9x | | 7(9d+8)=28 | | X(7x+5)=180 | | 3-3(-2b+2)=4(b-4)+3 | | 5x-10=12.5 | | 3p+9=0 | | 8-3(p-a)=2p | | 27=4p-9 | | -5-13=8x+17-7x | | h(-10)= | | 14/541n-454r | | -4x+9+5x=-10+7 | | X=3+-2 | | M(6x+5)=180 | | -18+7+(-3)=x | | 5(-.8+.4y)+4y=20 | | X-0.8=5.4 | | y^6-2y^3+y=0 | | 3/8=1/4p | | 5*-.8= | | x-8x+16=13 | | -15x-15y= | | 2(-2b+2)=-3(-4+b) | | 12x=-12+36 | | 3(2x+12)=-s(x-4)+x | | 0.03(m+7)=0.002(5-m)+0.03 | | 20x+15x-20(x-1)-15(x-1)=245 |